Status of Job Availability for Postgraduates in Geography Education (The Third Pole: Journal of Geography Education, 2021)
This paper attempts to analyze the situation of job availability in the markets for postgraduates, especially masters in geography education (M.Ed.). It also covers the scope of jobs in the markets, status of job involvement, and level of satisfaction based on qualitative research design and secondary data sources. Primary data were collection from interviews and discussions with teachers and postgraduate students of geography education. Secondary data were collection from various sources including digital libraries. The findings of this paper indicate that the postgraduate in Geography education is involved in different jobs such as teaching, educational research, administration, and educational planning in government, public and private sector institutions. Most of those who are engaged in teaching professions seem satisfied with their job. Besides, some private-sector workers are not happy with their work. Recently, the geography curriculum has offered geographic information systems (GIS), a global positioning system (GPS), and remote sensing (RS) as well as other tools and techniques. This may open ample job opportunities for geography graduates. The Department of Geography Education should be committed to producing skilled and competent man powers to fulfill market needs, and the government should make a policy arrangement to give priority in teaching, research, administration, and planning in education for the manpower produced in this subject.